"I Don't Belong Anymore": Undocumented Latino Immigrants Encounter Social Services in the United States. (August 2017) - Mallet, Marie L.; Calvo, Rocío; Waters, Mary C.
As undocumented Latino immigrants transition into adulthood, they also transition into illegality. They move from a somewhat protected status under which they had access to education and other social benefits, to the more vulnerable category of undocumented adults without access to social rights. How undocumented immigrants' interactions with social services contribute to the formation of their ethnic identity and feelings of belonging to the United States is the focus of this research. Drawing on qualitative interview data from undocumented adults who grew up in the United States, this article shows that as undocumented children transition into adulthood, they face a new system that forces them to learn how to become an immigrant if they want to remain part of American society.